2002
DOI: 10.1034/j.1600-0838.2002.120107.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle fatigue in long‐distance runners, sprinters and untrained men after repeated drop jumps performed at maximal intensity

Abstract: One hundred drop jumps were performed at maximal intensity every 20 s in 12 untrained subjects (UT), 9 sprinters (S) and 10 long-distance runners (LDR). Muscle contraction force (P20, P50) induced by percutaneous electrical stimulation (20 Hz and 50 Hz, respectively) as well as maximal voluntary contraction force and the height of vertical jumps performed in different ways decreased (P<0.05) and was not restored to the initial value 20 min post exercise. There was a marked increase in low frequency fatigue (LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 24 publications
7
35
0
11
Order By: Relevance
“…Evans et al [12] showed that endurance training of human muscle led to less damage following eccentric contractions while data from Patel et al [28] showed that, in rat muscles, increased oxidative capacity by electrical stimulation training did not result in less injury after eccentric exercise. Furthermore, Skurvydas et al [33] stated that endurance training and slow muscle fibre type prevalence does not result in less LFF, and neither does it accelerate the recovery of muscle contraction force following maximal, intermittent stretchshortening cycle exercise. However, in these studies it is difficult to determine if the different fibre types have been stretched to a similar extent.…”
Section: Possible Causes Of Lffmentioning
confidence: 98%
“…Evans et al [12] showed that endurance training of human muscle led to less damage following eccentric contractions while data from Patel et al [28] showed that, in rat muscles, increased oxidative capacity by electrical stimulation training did not result in less injury after eccentric exercise. Furthermore, Skurvydas et al [33] stated that endurance training and slow muscle fibre type prevalence does not result in less LFF, and neither does it accelerate the recovery of muscle contraction force following maximal, intermittent stretchshortening cycle exercise. However, in these studies it is difficult to determine if the different fibre types have been stretched to a similar extent.…”
Section: Possible Causes Of Lffmentioning
confidence: 98%
“…Muscle soreness was evaluated at 24, 48 and 72 h after the SSE. These muscle soreness evaluation methods have also been used in our previous researches [32,33].…”
Section: Muscle Sorenessmentioning
confidence: 99%
“…The equipment and technique for measuring the isometric torque of knee extensor muscles was the same as has been used in a previous study [28,32,33]. Subjects were placed in an experimental chair.…”
Section: Isometric Torque Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be due to SSC activity having both a rate (velocity) and magnitude (force) component in which a greater degree of concentric potentiation may exist following increased braking phase kinetics (Cavagna et al 1994;Finni et al 2001;Kyröläinen and Komi 1995;Viitasalo et al 1998). In comparisons of performance variables, DJs from various heights have been used to increase braking phase kinetics above that of the CMJ (Arampatzis et al 2001;Avela and Komi 1998;Bobbert et al 1987a, b;Häkkinen et al 1986;Kollias et al 2004;Skurvydas et al 2002;Viitasalo et al 1998). The DJ has been observed to produce significantly greater negative work and elicit increased muscle activity during the braking and pre-landing phases in comparison to the CMJ (Häkkinen et al 1986;Ishikawa et al 2003Ishikawa et al , 2004Ishikawa et al , 2005.…”
Section: Introductionmentioning
confidence: 97%